Studying the Thermal Effect and Nano Zinc Oxide Load Level on the Adhesion Between Rubber Compound and Steel Tire Cords (Journal of University of Babylon for Engineering Sciences, 2017)
In this research, T-adhesion of samples were evaluated at (25,50,75 and 100) °C temperature. The effect of nano-zinc oxide loading on rubber-tire cords interface is investigated by replacing of conventional zinc oxide by nano-zinc oxide as an activator. One compound has conventional zinc oxide as an activator with 8pphr (part per hundred rubber). Eight compounds have nano-zinc oxide with (0.2, 0.6, 1, 1.4, 1.8, 2.2, 2.6 and 4) pphr so as to improve adhesion force and reduce the amount of zinc oxide inside the compounds.The results show that the increasing temperature leads to decrease the adhesion in the rubber-tire cords interface. The maximum value of adhesion force with nano-zinc oxide is occurred at 2.2 pphr. The replacement of conventional zinc oxide by nano-zinc oxide leads to improve the pull-out force by 12%. Also, it reduces the amount of zinc oxide by 72.5%. Furthermore, it leads to reduce the cost of compounds. Finally, it reduces the negative effect of zinc oxide on the environment by reduction in the amount of zinc oxide inside the compounds.